Influenza vaccine effect on risk of stroke occurrence: a systematic review and meta-analysis - Zahhar, Jalal A.; Salamatullah, Hassan K.; Almutairi, Maher B.; Faidah, Dania E.; Afif, Lena M.; Banjar, Toka A.; Alansari, Nayef; Betar, Manar; Alghamdi, Saeed; Makkawi, Seraj (Frontiers in Neurology, 2024)
Background: Stroke is a significant global cause of mortality and long-term disability, potentially influenced by infections that heighten systemic inflammation and thrombotic events. The full impact of influenza vaccination on stroke remains uncertain. This systematic review and meta-analysis aimed to investigate the association between influenza immunization and stroke incidence. Methods: We searched for randomized controlled trials (RCTs), case-control, and cohort studies published in PubMed/Medline, Cochrane-Central-Register-of-Controlled-Trials (CENTRAL), and Embase until December 5, 2022, and identified articles investigating the effect of influenza vaccine on stroke occurrence. All articles were screened by two independent reviewers. We performed a meta-analysis to investigate the risk of stroke occurrence in vaccinated vs unvaccinated individuals. The random-effects model was used in all statistical analyses. Results: Among the 26 articles meeting our criteria, 10 were retrospective cohort studies, 9 were case-control studies, 3 were prospective cohort studies, 3 were RCTs and 1 case-series. Overall, the studies showed a significant decrease in the risk of stroke incidence/hospitalization among vaccinated patients (OR=0.81, 95% CI [0.77–0.86], P=0.00001). Furthermore, studies showed flu vaccine decreases the occurrence of mortality among stroke patients (OR=0.50, 95% CI [0.37–0.68], P=0.00001). Sub-group analysis revealed significant protective effect for patients with specific comorbidities including atrial fibrillation (OR=0.68, 95% CI [0.57–0.81], P=0.0001), diabetes (OR=0.76, 95% CI [0.66–0.87], P=0.0001), Chronic obstructive pulmonary disease (OR=0.70, 95% CI [0.61–0.81], P=0.00001), and hypertension (OR=0.76, 95% CI [0.70–83], P=0.00001). Conclusion: The current meta-analysis further supports prior findings that influenza vaccination reduces stroke risk, particularly in patients with comorbidities. Guidelines should promote vaccination for at-risk individuals.